Cross-cultural adaptation and validation of the Moral Distress Scale-Revised for nurses - Aline Marcelino Ramos; Edison Luiz Devos Barlem; Jamila Geri Tomaschewski Barlem; Laurelize Pereira Rocha; Graziele de Lima Dalmolin; Aline Belletti Figueira
ABSTRACT Objective: Cross-culturally adapt and validate the Moral Distress Scale-Revised for nurses. Method: Quantitative, analytical cross-sectional study conducted with 157 nurses of two hospital institutions of Southern Brazil, one public and one philanthropic. Procedures conducted: cultural adaptation of the instrument according to international recommendations; validation for the Brazilian context. Results: Face and content validation was considered satisfactory as assessed by a specialist committee and a pretest. The instrument demonstrated satisfactory internal consistency through frequency and intensity analysis per question in the 157 items and per subgroups of the various hospital units. Cronbach's alpha was 0.88 for the instrument and between 0.76 and 0.94 for hospital units. Pearson's correlation found a moderate association for moral distress among nurses. Conclusion: The Moral Distress Scale-Revised - Brazilian version is a valid instrument for the assessment of moral distress in nurses.